The diagnostic and prognostic role of miR-146b-5p in differentiated thyroid carcinomas - Ferraz, Carolina; Cunha, Gustavo Bittar; de Oliveira, Mariana Mazeu Barbosa; Tenório, Lucas Ribeiro; Cury, Adriano Namo; Padovani, Rosália do Prado; Ward, Laura Sterian (Frontiers in Endocrinology, 2024)
Samples classified as indeterminate correspond to 10-20% of cytologies obtained by fine needle biopsy of thyroid nodules, preventing an adequate distinction between benign and malignant lesions and leading to diagnostic thyroidectomies that often prove unnecessary, as most cases are benign. Furthermore, although the vast majority of patients with differentiated thyroid cancer (DTC) have such a good prognosis that active surveillance is permitted as an initial therapeutic option, relapses are not rare, and a non-negligible number of patients experience poor outcomes. MicroRNAs (miR) emerge as potential biomarkers capable of helping to define more precise management of patients in all these situations.Aiming to investigate the clinical utility of miR-146b-5p in the diagnostic of thyroid nodules and evaluating its prognostic potential in a real-world setting, we studied 89 thyroid nodule samples, correlating miR-146b-5p expression with clinical tools such as the 8th edition from the American Joint Committee on Cancer (AJCC/UICC) and the American Thyroid Association Guideline Stratification Systems for the rate of recurrence (RR). miR-146b-5p expression levels distinguished benign from malignant thyroid FNA samples (p<0.0001). For indeterminate nodules, overexpression of miR-146b-5p with a cut-off of 0.497 was able to diagnose malignancy with a 90% accuracy; specificity=87.5%; sensitivity=100%.An increased expression of miR-146b-5p was associated with greater RR (p=0.015). A cut-off of 2.21 identified cases with more vascular involvement (p=0.013) and a cut-off of 2.420 was associated with a more advanced TNM stage (p-value=0.047).We demonstrated that miR-146b-5p expression in FNA samples is able to differentiate benign from malignant indeterminate nodules and is associated with an increased risk of recurrence and mortality, suggesting that this single miRNA may be a useful diagnostic and prognostic marker in the personalized management of DTC patients.